Method of Teaching Arabic Language in Program Diniyah Formal (PDF) at Pondok Pesantren Al-Mubarak Wonosobo/طريقة تعليم اللغة العربية بالتربية الدينية الرسمية في معهد المبارك وونوسوبو - Kurniasih, Novita (UIN Raden Mas Said Surakarta, 2020)
This study aims to find out the Arabic language learning method at Pondok Pesantren Al-Mubaarak Wonosobo year lesson 2018/2019. This research uses qualitative type. Located at the Islamic boarding school Al-Mubaarak Wonosobo in January 2019-March 2019. The subject in this study is the Arabic language teacher and students at the Islamic boarding school Al-Mubaarak Wonosobo. Methods of collecting data with observations, interviews, and documentation. Test the validity of the data by using source triangulation. Data analysis starts with data collection, data reduction, and data presentation and delivery. The conclusion of this research is the method of learning Arabic at the Islamic boarding school Al-Mubaarak Wonosobo by using the method Grammer Translation, method of the audio-lingual, direct method. and electric method.